P14.67 Somatostatin receptor targeted radioligand therapyin head and neck paraganglioma. (6th September 2019) - Müther, M; Roll, W; Stegger, L; Zinnhardt, B; Schäfers, M; Weckesser, M; Rahbar, K; Stummer, W
Abstract: BACKGROUND: Surgical resection is the therapy of choice in head and neck paraganglioma. However, surgery is associated with significant morbidity depending on tumor size and localization. In case of progressive residual or recurrent disease, new and less aggressive therapeutic options are warranted. Somatostatin receptor (SSTR) targeted therapies pose a promising alternative, as SSTRs are upregulated in paragangliomas. Only few studies provide evidence on efficacy of 177Lu-DOTATATE therapy in these patients. The aim of this study was to evaluate the efficacy of peptide receptor radiotherapy (PPRT) with 177Lu-DOTATATE for head and neck paragangliomas. METHODS: A total of seven consecutive patients (mean age: 60 years, range: 14–84) with progressive head and neck paragangliomas (3 carotid body tumors, 4 jugulotympanic paragangliomas), treated with PRRT using 177Lu-DOTATATE, were included in this retrospective analysis. Therapy response was assessed by interim and post-therapy 68Ga-DOTATATE-PET-CT and MRI according to morphological and SSTR imaging parameters. Therapeutic uptake was classified on177Lu-DOTATATE scintigraphies 48h p.i. according to the Krenning scale. Longer-term clinical and imaging-based outcome were evaluated. RESULTS: Patients received a median of 4 cycles (range: 3 to 5) of PRRT with 177Lu-DOTATATE (mean injected dose 7.3 GBq). Interim and post-therapy staging showed at least stable disease in all patients. Tumor uptake in 48h p.i. 177Lu-scintigraphies was moderate to high in all patients (Krenning scale; median: 3; range: 2–4). Furthermore, none of the patients showed progressive disease during the median follow-up time of 28 months (range: 6–37 months). CONCLUSION: SSTR targeted therapy using 177Lu-DOTATATE shows promising efficacy and may lead to long lasting stable disease.